Clinical Impact of ACE-I/ARB for Conservatively Treated Patients with Moderate to Severe Mitral Regurgitation: A Single Center Observational Study - Robert Uzel; Raphael R. Bruno; Christian Jung; Christian Lang; Hannes Hoi; Martin Grünbart; Christian Datz; Friedrich Hoppichler; Bernhard Wernly (Journal of Cardiovascular Development and Disease, 2023)
(1) Background: Mitral regurgitation (MR) is associated with increased mortality and frequent hospital admissions. Although mitral valve intervention offers improved clinical outcomes for MR, it is not feasible in many cases. Moreover, conservative therapeutic opportunities remain limited. The aim of this study was to evaluate the impact of ACE inhibitors and angiotensin receptor blockers (ACE-I/ARB) on elderly patients with moderate-to-severe MR and mildly reduced to preserved ejection fraction. (2) Methods: In total, 176 patients were included in our hypothesis-generating, single-center observational study. Hospitalization for heart failure and all-cause death have been defined as the combined 1-year primary endpoint. (3) Results: Patients treated with ACE-I/ARB showed a lower risk for the combined endpoint of death and heart failure-related readmission (HR 0.52 95%CI 0.27–0.99; p = 0.046), even after adjustment for EUROScoreII and frailty (HR 0.52 95%CI 0.27–0.99; p = 0.049) (4) Conclusions: The use of an ACE-I/ARB in patients with moderate-to-severe MR and preserved to mildly reduced left-ventricular ejection fraction (LVEF) significantly associates with improved clinical outcome and might be indicated as a valuable therapeutic option in conservatively treated patients.